On Bank Consolidation in a Currency Union - Di Vittorio, Fabio (IMF Working Papers; Working Paper ;, 2018)
The paper focuses on the impact of diversification on bank performance and how consolidation through mergers and acquisitions (M and A) affects the banking sector's stability in the Eastern Caribbean Currency Union (ECCU). The paper finds that a lower level of loan portfolio diversification explains higher non-performing loans and earnings volatility of indigenous banks, as compared to foreign competitors in the ECCU. We then simulate bank mergers both within and across ECCU countries by combining individual banks' balance sheets. The simulation shows that a typical indigenous bank could better diversify against its idiosyncratic risk by merging with other banks across the border. In addition, we point out that M and A, leading to a more asymmetric banking sector, may increase systemic risk.